Burnout Syndrome and Quality of Working Life among Health Services Professionals - Flores, Noelia; Jenaro, Cristrina; Cruz, Maribel; Vega, Vanessa; Pérez, María del Carmen (Pensando Psicología, 2013)
The aim of this study was to analyze factors associated with the quality of work life and their relationship to burnout among health care professionals. The sample consisted of 562 workers from the health sector, who were evaluated in relation to their stressors or job demands, perceived social support, burnout syndrome, various biopsychosocial health factors and their satisfaction with and perceived quality of working life. The instruments used were the MBI-GS, the Job Content Questionnaire (JCQ) and the Goldberg General Health Questionnaire (GHQ-28). The results showed high levels of perceived stress and the presence of burnout. There were also impacts on physical and psychological health. The analysis of variance revealed the existence of significant differences in variables such as professional category and length of service. Furthermore, regression analysis confirmed that the quality of working life experienced by medical personnel is the result of a balance between demands, resources and lack of burnout. These results support the need to intervene with these professionals to improve their health as well as the quality of services provided.